RURAL-URBAN DIFFERENCE IN LEVELS OF PHYSICAL ACTIVITY AMONG HAUSA-FULANI OF NORTH-WESTERN NIGERIA - ANAS AS; SANDRA OI; SANI AA; ABUBAKAR SM; AUGUSTINE EO; KABIRU S (Ntec Specialist, 2015)
Lifestyles, including physical inactivity are known risk factors for cardiovascular diseases. Urbanization has been associated with physical inactivity. Objective: The objective of this study was to determine the level of physical activity among the Hausa Fulani of Sokoto, Nigeria and to compare physical activity levels between rurul and urban Hausa Fulani of the sub-region. Method: This was a cross-sectional study conducted in Sokoto State in Northern Nigeria using multistage sampling design. Seven hundred and eighty two participants were recruited. Using the WHOSTEP wise approach to surveillance (STEP) Instrument, information on socio-demographic, physical activity and anthropometric data was obtained. Being physically active was defined as participating in 30 or more minutes of moderate or vigorous activity per day for at least 5 days in a week. Results: The mean (SD) age of the study population was 38.9 (36.6) years. Four hundred and sixty two (59.0%) subjects comprising of 182 (46.8%) and 280 (71.2%) from the urban and rural locations respectively, were physically active. The male subjects (64.1%) were more physically active than the females (53.6%) (P=0.002). Occurrence of physical inactivity in the Hausa-Fulani increases with increased age and body mass index. Conclusion: Physical inactivity is common among the Hausa-Fulani ethnic group of North-Western Nigeria. It is commoner in the urban compared to the rural dwellers. There is therefore the need for public health interventions to improve physical activity so as to reduce the risk of non-communicable diseases associated with physical inactivity